The Prevalence of Endodontic Instrument Separation in Patients of Faculty of Dentistry in Hama University – A Retrospective Radiographic Study - (Journal of Hama University, 2021)
Instrument separation during root canal therapy is very disturbing event for the dentist and is considered as problem we cannot avoid yet, even with the skillful hands. So that, we have to make it as minimum as possible using well knowledge of its causes and mechanisms. This study investigated the prevalence of instrument separation (IS) within the previously treated teeth in a sample of the panoramic radiographic images of patients at the faculty of dentistry of University of Hama according to three variables: (tooth type, the third of root canal, separated instrument’s length). In 791 cases, the incidence of IS was 7.58%.The probability of separating an instrument in apical third was 94%, while in coronal and middle thirds of the canals were only 3% for each . The highest percentage of IS occurred in mandibular (55%) and maxillary (25%) molars. Furthermore, there was a statically significant difference in IS according to its length, the prevalence of short instrument (3mm) was 15% only. The data obtained is statistically analyzed using Chi-Square of independent means test. (P